2012
DOI: 10.1073/pnas.1118378109
|View full text |Cite|
|
Sign up to set email alerts
|

Biased learning affects mate choice in a butterfly

Abstract: Early acquisition of mate preferences or mate-preference learning is associated with signal diversity and speciation in a wide variety of animal species. However, the diversity of mechanisms of mate-preference learning across taxa remains poorly understood. Using the butterfly Bicyclus anynana we uncover a mechanism that can lead to directional sexual selection via mate-preference learning: a bias in learning enhanced ornamentation, which is independent of preexisting mating biases. Naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 56 publications
3
114
0
Order By: Relevance
“…Behavioural flexibility may further accelerate divergence by exposing organisms to new selection regimes. In other taxa, behavioural plasticity has been linked to range and niche expansion (Sol et al ., ; Gonda et al ., ), variation in host use (Snell‐Rood & Papaj, ; Nylin et al ., ) and mate choice (Svensson et al ., ; Westerman et al ., ).…”
Section: Understanding Adaptation Within Its Ecological Contextmentioning
confidence: 99%
“…Behavioural flexibility may further accelerate divergence by exposing organisms to new selection regimes. In other taxa, behavioural plasticity has been linked to range and niche expansion (Sol et al ., ; Gonda et al ., ), variation in host use (Snell‐Rood & Papaj, ; Nylin et al ., ) and mate choice (Svensson et al ., ; Westerman et al ., ).…”
Section: Understanding Adaptation Within Its Ecological Contextmentioning
confidence: 99%
“…B. anynana were reared at 27°C, 80% humidity, as previously described (40). Upon eclosion, virgin male and female adults were isolated from one another to ensure virginity and were kept in cooler conditions (17°C) until all animals of that generation emerged and were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of other butterfly genera, such as those of the family Nymphalidae, have shown that dorsal wing patterns function primarily as sexual signals [5456] whereas ventral patterns mostly aid in deterring predation [43, 57, 58]. The most likely explanation for the signal partition between dorsal and ventral surfaces is that, barring those species that upon sensing danger have a wing flashing display [59], most butterflies fold and hold their wings over their body, and primarily expose their ventral wing surfaces even during an attack.…”
Section: Discussionmentioning
confidence: 99%